PERANCANGAN KATALOG TARI BANDENG NENER MENGGUNAKAN MEDIA FOTOGRAFI SEBAGAI UPAYA PELESTARIAN BUDAYA DI SIDOARJO - Moh Fatkhul Awaludin; Putra Uji Deva Satrio (DESKOVI : Art and Design Journal, 2024)
Fotografi dapat digunakan untuk memperkuat gambar dalam banyak hal, seperti menjaga kearifan lokal. Penelitian ini bertujuan untuk membuat katalog yang menggambarkan tari Bandeng Nener, yang berasal dari Sidoarjo. Penelitian ini menggunakan pendeketan penelitian kualitatif berdasarkan data yang diperoleh dari wawancara. Hasil penelitian menunjukkan bahwa katalog tari Bandeng Nener difoto dengan sentuhan gaya kontemporer; perancangan dimaksudkan untuk memberikan gambaran tari tradisional yang lebih modern. Katalog fotografi tari Bandeng Nener ini dirancang untuk membantu menjaga kebudayaan tradisional dan memberi masyarakat Indonesia media informasi. Dengan menyertakan sejarah dan penjelasan rinci tentang tarian Bandeng Nener, katalog fotografi tarian tradisional akan menjadi angin segar untuk budaya tradisional dengan mengangkat tema kebudayaan tarian tradisional. Photography can be used to strengthen the image in many ways, such as maintaining local wisdom. Bandeng Nener dance is a little-known traditional dance from Indonesia, depicting the life of coastal communities and cultural rituals. This dance is often featured in local ceremonies and festivals to celebrate the abundance of marine products and honor ancestors. This study aims to create a catalog that describes the Nener Bandeng dance, which comes from Sidoarjo. The purpose of making Nener Bandeng dance catalog is to document and preserve this traditional dance so that it does not become extinct and remains known by future generations. This catalog also provides complete and accurate information for students, researchers, and the general public who want to learn more about Bandeng Nener dance. This study uses a qualitative research approach based on data obtained from interviews. Researchers also used the case study method by analyzing the messages in photographs from several photographers on social media related to culture and cultural promotion. This Data is used as a reference in the discussion chapter and is presented in the form of a descriptive narrative. The results showed that the Nener Bandeng dance catalog was photographed with a touch of contemporary style. The design is intended to provide an overview of traditional dance more modern. The storyline in Bandeng Nener dance catalog includes an explanation of each dance. On the cover, the process involved creating several design alternatives with the aim of obtaining results that fit the concept. The colors used within the pages of this catalog vary, each having a different meaning.